Juridical Analysis of the MBKM Internship Program from the Perspective of Employment Law and Constitutional Law: Between Fulfilling Student Rights and Obligations of Educational Institutions - S.T. Kansil, Christine; Parapat, Fauzan Rizki (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
This research aims to analyze the impact of the Freedom to Learn-Independent Campus (MBKM) Program on students' rights in the context of higher education in Indonesia. The MBKM Program is expected to bridge the gap between education and industry, providing students with opportunities to develop practical skills. However, this research identifies several challenges faced by students, particularly concerning their legal status as interns and the protection of their labor rights. The research employs a qualitative analysis method with a case study approach, which includes interviews and the collection of secondary data from relevant documents and reports. The findings indicate that although the MBKM Program offers significant benefits in enriching students' learning experiences, the current regulations remain unclear and lack sufficient oversight, which may lead to exploitation. Therefore, this research recommends the need for harmonization between educational and labor regulations, as well as strengthening oversight systems to ensure the protection of students' rights. This study aims to contribute to the development of fairer and more sustainable education policies in Indonesia.